2011
DOI: 10.1007/s12275-011-1122-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristization of propionyl-coenzyme a carboxylase complex of Streptomyces toxytricini

Abstract: Acyl-CoA carboxylases (ACC) are involved in important primary or secondary metabolic pathways such as fatty acid and/or polyketides synthesis. In the 62 kb fragment of pccB gene locus of Streptomyces toxytricini producing a pancreatic inhibitor lipstatin, 3 distinct subunit genes of presumable propionyl-CoA carboxylase (PCCase) complex, assumed to be one of ACC responsible for the secondary metabolism, were identified along with gene for a biotin protein ligase (Bpl). The subunits of PCCase complex were a subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…2) [12,229]. These enzymes are different from PCC (family 1.5) in that they probably lack the BT domain in the α subunit.…”
Section: Other Acyl-coa Carboxylasesmentioning
confidence: 99%
“…2) [12,229]. These enzymes are different from PCC (family 1.5) in that they probably lack the BT domain in the α subunit.…”
Section: Other Acyl-coa Carboxylasesmentioning
confidence: 99%
“…Although the removal of GlnB protein relieved its inhibition of ACC and PCC, increasing the yield of FK520 to a certain extent, the content of methylmalonyl-CoA in the late period of fermentation was still low ( Figure 4D ). Previous research suggested that the specific β subunit (responsible for substrate recognition) and ε subunit (responsible for protein- protein interactions) are crucial for the carboxylation activity of PCC ( Diacovich et al, 2002 ; Demirev et al, 2011 ; Tong, 2013 ). The results of amino acid sequence alignment showed that the 1_3398 gene ( pccB ) encoded the β subunit, while the 1_3397 gene ( pccE ) encoded the ε subunit of PCC in S. hygroscopicus var.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it was speculated that ACC and PCC might both be regulated by PII proteins in actinobacteria ( Figure 1A ). Since the carboxylation products of these two enzymes, malonyl-CoA and methylmalonyl-CoA, are important precursors for the biosynthesis of polyketide antibiotics ( Rodriguez et al, 2001 ; Demirev et al, 2011 ), it is of great significance to explore the influence of PII proteins on the activity of ACC and PCC, with the aim of improving the antibiotic yield.…”
Section: Introductionmentioning
confidence: 99%
“…Such proteins act as carboxyl transferases involved in precursor supply in fatty acid or polyketide biosynthesis. [12] Phn2 revealed 47 % identity to a gene encoding for a PKS of Streptomyces violaceusniger Tu 4113 (Table 1). A detailed analysis of the 22 kb gene gave evidence for the presence of a complete PKS consisting of five modules.…”
Section: Sequence Analysis Of the Phenylnannolone A Biosynthetic Genesmentioning
confidence: 99%